Exploring and Critiquing Women’s Academic Identity in Higher Education: A Narrative Review - Phillips, Matty; Dzidic, Peta; Castell, Emily (SAGE Publications, 2022)
Academia has been characterized as traditional, hierarchical, and selective, founded on patriarchal, imperial, and colonial values that construct and maintain gendered roles and regulations. This has been proposed to disadvantage how women experience, and identify within, academia. A narrative review was conducted to review the literature on women’s academic identities and experiences, and critique the dominant ways of knowing, being, and doing in academia. Thematic synthesis was conducted on 56 qualitative studies (published 2010–2019), illustrating the impact of these values on women’s academic identities and experiences, and normative gendered stereotypes and practices that impact women academics. Furthermore, existing literature is critiqued, exploring the influence of dominant ways of being and knowing (on how questions are asked, the constructs explored, the design decisions made). By providing this commentary, future research can focus on problematizing the system and dismantling the problematic conditions (e.g., underrepresentation, discrimination, and gendered stereotyping) for women in academia.